LEGAL PROTECTION ON APARTMENT UNIT PURCHASER IN RELATED TO THE OWNERSHIP - Saputra, Athalia (Tadulako Law Review, 2018)
The sale and purchase's binding agreement is often becomes a temporary hold for buyer of apartment units over the years. In every sale and purchase's binding agreement always made by developer only, beside that sale and purchase's binding agreement had a standard character and not detail, because there are still many things to be done in the process of splitting certificate. But this is becoming a sudden concern for developers, how if something wrong happens with the developer. every buyer has no proof of ownership yet. It is a dangerous thing for buyer. Proof of ownership to buyers is sale and purchase’s agrrement who made by Pejabat Pembuat Akta Tanah in Indoensia. Research conducted using normative juridical research, which faces legal issues with the process of discovering legal rules, legal principles, and legal doctrines relating to the issue of law. In this study used deductive method that begins from the things that are common then applied to the formulation of the problem and can produce answers that are specific and legitimate. Based on the results of research, from the various rules of law, doctrine, In Indonesia regulates the legal provisions for buyers where buyers can apply for legal remedies through courts of law in Indonesia. The regulation which regulated are Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen dan Undang-Undang Nomor 20 Tahun 2011 tentang Rumah Susun.